Technological progress and other factors behind the adoption of electric vehicles: Empirical evidence for EU countries - Neves, Sónia Almeida (2019)
This paper aims to analyse the factors supporting the transition to new forms of mobility, namely Electric Vehicles (EV). For a deep understanding of these effects, we analysed EV, by dividing them into individual Battery Electric Vehicles (BEV), which are 100% electric, and Plug-in Hybrid Electric Vehicles (PHEV). The factors examined include: policy, social, economic, environmental, and technical. This paper uses data from 2010 to 2016 for a panel of the 24 EU countries. A Panel-Corrected Standard Errors (PCSE) estimator is used. When comparing the results of analysing BEV and PHEV individually, and all EV together, they prove to be quite different. This finding indicates that policies should be tailored to each individual technology, rather than a single one for all EV. The proxy used for technological progress is the increased use of both BEV and PHEV. The evidence is also provided that charging stations are drivers of electric mobility.